2017
DOI: 10.1007/s12035-017-0532-4
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Strategies Under Development Targeting Inflammatory Mechanisms in Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurological disease characterized by the progressive loss of cortical, bulbar, and spinal motor neurons (MNs). The cardinal manifestation of ALS is a progressive paralysis which leads to death within a time span of 3 to 5 years after disease onset. Despite similar final output of neuronal death, the underlying pathogenic causes are various and no common cause of neuronal damage has been identified to date. Inflammation-mediated neuronal injury is increasingly recognize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 211 publications
2
36
0
Order By: Relevance
“…Finally, a larger sample of human SOD1 mutation carriers could aid to prove our theory. With additional evidence, our simple procedure may help to identify patients with ALS with a constellation of peripheral nerve immunity, permitting them to be selectively enrolled into therapeutic trials targeting PNS inflammation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a larger sample of human SOD1 mutation carriers could aid to prove our theory. With additional evidence, our simple procedure may help to identify patients with ALS with a constellation of peripheral nerve immunity, permitting them to be selectively enrolled into therapeutic trials targeting PNS inflammation …”
Section: Discussionmentioning
confidence: 99%
“…It could be of pivotal importance for the development of new therapies to selectively stratify patients in vivo who display certain pathobiologies—such as immune activation—that are, in turn, likely to respond to specific therapeutic agents . In fact, not all patients with ALS manifest a strong inflammatory component; underpowered trials with insufficient differentiation of that possibly rather small patient group may thus account for the modest effects of immune‐modulating drugs in ALS . To this end, simple measures that can specifically identify those patients with disease‐related suspected immune activation are desirable.…”
mentioning
confidence: 99%
“…Our findings also suggest that the pathology‐specific interaction between TRPC3 and Nox2 could be a general mechanism underlying wasting in a range of tissues. Indeed, ibudilast has pleiotropic effects on amyotrophic lateral sclerosis and multiple sclerosis (Crisafulli, Brajkovic, Cipolat Mis, Parente, & Corti, ; Fox et al, ). Further studies will elucidate the involvement of TRPC3‐Nox2 complexes in these intractable diseases and allow us to propose the inhibition of TRPC3‐Nox2 complex as an innovative therapeutic strategy for their prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence for both central and peripheral immune system activation in ALS. In early disease, there is evidence of homeostatic microglia and Treg infiltration, while in later disease stages, M1 microglia and activated astrocytes predominate (157). Tregs themselves are defective in ALS (99,100).…”
Section: Immune-directed Therapies For Neurodegenerative Diseasesmentioning
confidence: 99%
“…It failed two earlier trials in people with all stages of ALS. Other immune-directed strategies currently under investigation include ibudilast, anti-IL-6 (tocilizumab), and IL-1 receptor antagonist (anakinra) therapies (157). We have found that both microglia and peripheral monocytes have an inflammatory phenotype in the SOD model and in ALS and that targeting miR-155 ameliorates disease in this model (91); targeting of miR-155 is now being evaluated in clinical trials.…”
Section: Immune-directed Therapies For Neurodegenerative Diseasesmentioning
confidence: 99%